WHATSAPP VOICE CHAT (WVC) AS AN EFL ONLINE LEARNING MEDIA - Adia Budjana; Achmad Anang Darmawan; Lina Aris Ficayuma (Journal of English Language Teaching and Islamic Integration, 2023)
In  recent  years,  researcher  interested  in  mobile-assisted  language  learning  (MALL)  for online learning of English as a foreign language (EFL). In the current era of digitalization, access to information and materials can be easily found in cyberspace, either by accessing a page or by using an application. With these advances in technology, can be used as a tool to facilitate the educational  process.  The  Ministry  of  Education  and  Culture  is  aware  of  the  current  needs,because by utilizing technology it can reach and distribute broad policies, as well as optimize the implementation  of  the  Merdeka  curriculum. As a  teacher, this  is  a  challenge  in  itself  to bring students  to  learning  transformation,  where  the  teacher  acts  as  a  facilitator  to  encourage  the learning process.